Instilling of Environmental Love Character Through Tadabbur Alam Activities to Develop Suistanable Development Goals (SDGs) - Reswari, Ardhana; Iftitah, Selfi Lailiyatul; Prastyo, Danang (Entita: Jurnal Pendidikan Ilmu Pengetahuan Sosial dan Ilmu-Ilmu Sosial, 2025)
Instilling of environmental love character is important to be applied to early childhood through nature-based education, given the increasing environmental problems that require serious attention. One method that is expected to have a positive impact is the activity of Tadabbur Alam. This study aims to examine instilling of environmental love character through Tadabbur Alam activities in children at RA Adirasa Jumiang and its contribution to clean social awareness. This research uses a descriptive qualitative approach, where data is obtained through interviews, observations, and documentation of activities. The results showed that Tadabbur Alam activities succeeded in increasing children's awareness of the importance of preserving nature, as well as building a sense of social responsibility for the surrounding environment. The children involved in this activity showed a more caring attitude towards cleanliness and environmental sustainability. In addition, this activity also plays a role in strengthening clean social values, such as responsibility and cooperation. This research contributes to broadening the understanding of how nature-based education can support the character building of children who care more about the environment and society.